Elementary differential geometry - O'Neill, Barrett (Elsevier Academic Press, 2006)
Written primarily for students who have completed first courses in calculus and linear algebra, this textbook provides an introduction to the geometry of curves and surfaces. This revised second edition gives an update of commands for the symbolic computation programs Mathematica or Maple.